CRITICAL REALISM OF AL-KINDÎ ON ARISTOTLE'S THEORY OF CREATION - Nur Hadi Ihsan; Elit Ave Hidayatullah; Sofyan Atstsauri (University of Darussalam Gontor Press, 2023)
This study aims to expose al-Kindi's theory of creation and his repudiation of Aristotle's equivalent theory. The theory of creation was one of the philosophical problems that originated in the Greco-Aristotle philosophy. In this tradition,